Exploring Gender and Subjectivity in Narrative Research - Malm, Birgitte (Narrative Matters, 2011)
In this article, Anna’s occupational life history has been chosen to illustrate one woman’s personal and professional struggle for purpose and identity. Subjective construction is an on-going process and roles and identities are in a constant flux of coping with the tensions between continuity and change. By partaking of private as well as professional experiences, strategies used to maintain Anna’s personal integrity in changeable and often demanding contexts become clearer. Based on interviews, reflections, and discussions, Anna’s story provides authentic insights into the ways in which one teacher has learnt to cope with the demands and challenges in her life.